Gender differences in major adverse cardiovascular outcomes among aged over 60 year-old patients with atherosclerotic cardiovascular disease: A population-based longitudinal study in Taiwan - Lee, Meng-Kuang (Medicine (Baltimore), 2020)
Atherosclerotic cardiovascular disease (ASCVD) including cerebrovascular disease (CVD), coronary artery disease (CAD), and peripheral arterial disease (PAD), contributes to the major causes of death in the world. Although several studies have evaluated the association between gender and major adverse cardiovascular outcomes in old ASCVD patients, the result is not consistent. Hence, we need a large-scale study to address this issue. This retrospective cohort study included aged over 60 year-old patients with a diagnosis of ASCVD, including CVD, CAD, or PAD, from the database contained in the Taiwan National Health Insurance Bureau during 2001 to 2004. The matched cohort was matched by age, comorbidities, and medical therapies at a 1:1 ratio. A total of 9696 patients were enrolled in this study, that is, there were 4848 and 4848 patients in the matched male and female groups, respectively. The study endpoints included acute myocardial infarction, hemorrhagic stroke, ischemic stroke, vascular procedures, in-hospital mortality, and so on. In multivariate Cox regression analysis in matched cohort, the adjusted hazard ratios (HRs) for female group in predicting acute myocardial infarction, hemorrhagic stroke, ischemic stroke, vascular procedures, and in-hospital mortality were 0.67 (P < .001), 0.73 (P = .0015), 0.78 (P < .001), 0.59 (P < .001), and 0.77 (P = .0007), respectively. In this population-based propensity matched cohort study, age over 60 year-old female patients with ASCVD were associated with lower rates of acute myocardial infarction, hemorrhagic stroke, ischemic stroke, vascular procedures, and in-hospital mortality than male patients. Further prospective studies may be investigated in Taiwan.